O Colegiado Territorial do Mato Grande em movimento: representação política e sua influência na participação e debate sobre desenvolvimento territorial - Anjos, Eucástila Jordânia de Souza Dias (2016)
The rural development policy in Brazil has the territorial approach as a strategy and established a few years ago the creation of spaces for diverse social participation, called Council or territorial forums. These spaces should be attended by representatives of various segments of society that make up the political dynamics of the territories: civil society organizations (NGOs, trade unions, associations, unions, social movements, etc.) and public managers (municipal and state secretaries, local authorities and agencies federal as MDA). This work aims to analyze the relations between political representatives considered central in the debate and enforcement actions with territorial focus in Mato Grande / RN. Focus on the influence of their actions in the field conformed discussions from the institutionalized space of participation, the Territorial Council, established under the guidance of this strategy in 2005 as the body of management and social control of state actions. We also seek to understand from the trajectories of these representatives and mobilizing the concept of fields (Bourdieu, 1989.2002) as streamline, influence the internal organization, agendas and decision making in representation spaces (Council and Director Center). Building on participants made observations, as well as in semi-structured interviews with agents considered central, can be glimpsed elements that bring these trajectories. Originating Family Agriculture, the central representatives can exercise the symbolic power (Bourdieu, 1989) in the field of debates and interests and have common points in their trajectories as transit through social and service organizations movements. Processes that reproduce in a context of neglect of municipal administrations and state with this debate, a factor that would condition the reproduction of a low social participation environment surrounding the promotion of rural development, then the perspectives brought by the territorial approach.